Assessment of the sustainability of organization development in the process of strategic controlling - A. R. Khachemizov; V. I. Zarubin; A. K. Dorgushaova (Новые технологии)
Development of an enterprise in a market environment is a complex process of interaction and mutual influence of multidirectional factors. This requires effective control, which allows not only to determine the operational state of an enterprise, but also to assess its strategic stability in the future. In this regard, the relevance of the search for effective tools for assessing the sustainability of an enterprise in the process of strategic control increases. The purpose of the research is to develop guidelines for assessing the sustainability of an enterprise based on an analysis of existing theoretical approaches. The methodological basis of the research is a structural and functional approach, which provides for taking into account not only functional, but also structural aspects in the methodology for assessing the sustainability of an enterprise. To achieve the goal of the research the following methods were used: theoretical generalization, analysis and synthesis, system approach, comparative and structural analysis. The system of indicators for the development of an economic entity, which makes it possible to assess the stability of an enterprise in quantitative, qualitative and structural components, which contributes to an increase in the level of validity of decisions, as well as an algorithm for an integral assessment of the development of an enterprise, which makes it possible to implement strategic controlling of enterprise stability have become the results of the research. The scientific novelty of the proposed materials lies in the development of theoretical and methodological approaches to assessing the sustainability of enterprise development in the process of strategic controlling. Theoretical significance of the research lies in the development of methodological foundations for the formation of an effective system of strategic controlling at an enterprise. The practical significance lies in the substantiation of tools for assessing the sustainability of an enterprise in a strategic perspective. The results can be used in strategic enterprise management. Formation of an adequate, reliable and objective information base for assessing the sustainability of its development is a prerequisite for effective strategic controlling. On this basis further analysis is carried out and measures are developed to improve the management process. Assessment of development sustainability is an important part of controlling the functioning of an enterprise.